Design of curved radome-antenna system - Li, Yikun (Nanyang Technological University, 2022)
As the antenna systems developed, the requirement of the operating performance of those systems are becoming more and more strict. Only by designing the structure of the antenna is difficult to meet those requirements. Therefore, cascading the radome and the antenna system is a great way to solve the problem. The basic working principle of the radome-antenna system is to ensure the there is no interference EM wave while the EM wave in working band will be transmitted or received successfully. However, the out of band frequency wave will be reflected, resulting in high Radar-Cross-Session (RCS) of the objective and the signature of radar. By integrating the radome and the antenna system carefully, radome will create a transmission window of the desired frequency band while absorb the rest frequency band. In this thesis, two kinds of rasorber will be presented. Two kinds of radomes composed of those two rasorbers will also be simulated and analyzed. This dissertation will focus on S-parameters of rasorbers while Radiation Patterns and Monostatic RCS of radomes. The single-polarized rasorber has a transmission band from 3.5 GHz to 4.3 GHz with a 26.8% and 125.6% transmission bandwidth and fractional bandwidth respectively. The Monostatic RCS of the radome constructed by the rasorber will be significantly reduced for both curved and planar one. The dual-polarized rasorber has a transmission band of 27.8% from 7.4 GHz to 9.8 GHz. The performance of both dual-polarized planar and curved radome will be presented and analyzed.